2003
DOI: 10.1016/s0020-7292(03)00276-5
|View full text |Cite
|
Sign up to set email alerts
|

Drotaverine hydrochloride for augmentation of labor

Abstract: Drotaverine hydrochloride is safe and effective in accelerating labor, but not effective in lessening labor pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 4 publications
3
47
2
Order By: Relevance
“…Regarding the duration of 3 rd stage of labor in the present study, the mean time was shorter in HBB group. This result is near to the study done by Singh KC et al (2004) which showed that the mean time of 3 rd stage of labor was about 9.33minutes 13 . C/S and assisted vaginal delivery rates in this study were comparable to the result found by Shobha et al (2006) which showed the rate of spontaneous vaginal delivery was 84% with only one case of C/S and about 15% of assisted vaginal delivery 12 .…”
Section: Methodssupporting
confidence: 72%
“…Regarding the duration of 3 rd stage of labor in the present study, the mean time was shorter in HBB group. This result is near to the study done by Singh KC et al (2004) which showed that the mean time of 3 rd stage of labor was about 9.33minutes 13 . C/S and assisted vaginal delivery rates in this study were comparable to the result found by Shobha et al (2006) which showed the rate of spontaneous vaginal delivery was 84% with only one case of C/S and about 15% of assisted vaginal delivery 12 .…”
Section: Methodssupporting
confidence: 72%
“…9 Although methods to increase uterine contractility such as amniotomy and oxytocics are also used to accelerate cervical dilatation, but these methods are also associated with complications. 10 In the present study we observed an initial cervical dilatation to be lying in the range of 3-4 cm ( Table 2).…”
Section: Discussionsupporting
confidence: 61%
“…Similarly for drotaverine hydrochloride too Table 6: Distribution of subjects in three groups according to mode of delivery. 14 Khosla et al, 15 Singh et al 10 Have shown a proven efficacy of drotaverine hydrochloride over placebo and other drugs. These results are in agreement with our study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5 The incorporation of partogram was helped to earlier recognition of dystocia and implementation of measures at the same time. 7 There was no major difference in the percentage of normal delivery in the study as well as control groups. This was in accordance with the observations of other studies.…”
Section: Discussionmentioning
confidence: 67%